Acute hepatitis C treatment in advanced renal failure using 8 weeks of pan-genotypic daclatasvir and reduced-dose sofosbuvir. Issue 10 (23rd October 2020) - Goel, Amit; Bhadauria, Dharmendra S; Kaul, Anupma; Verma, Abhai; Tiwari, Prachi; Rungta, Sumit; Rai, Praveer; Gupta, Amit; Aggarwal, Rakesh
Abstract: Background: Sofosbuvir is not recommended in persons with estimated glomerular filtration rate (eGFR) <30 mL/min. We report the results of treatment with an off-label 8-week regimen of daclatasvir and half-dose sofosbuvir in patients with acute infection with hepatitis C virus ( HCV) and eGFR <30 mL/min. Methods: Clinic records were searched to identify treatment-naïve, noncirrhotic adults with acute hepatitis C (HCV viremia and a ≥10-fold elevation of serum alanine aminotransferase activity) and eGFR <30 mL/min, who had been treated with a sofosbuvir-based regimen. Treatment response was assessed using serum HCV RNA testing at 4 weeks of treatment, end of the 8-week treatment and 12 weeks after stopping treatment. Results: Of the 31 patients with acute hepatitis C, 27 [median age (range): 36 (18–74) years; 20 (74%) male] were started on treatment with 200 mg sofosbuvir and 60 mg daclatasvir daily for 8 weeks, irrespective of HCV genotype. All the 27 completed the planned 8-week treatment. One patient died 10 weeks after completing the treatment of an unrelated cause. All the 27 patients had undetectable HCV RNA after 4 weeks of and at the end of treatment. At 12 weeks after completion of treatment, only one tested HCV RNA positive and 25 were negative, with sustained virological response rate of 25/27 (92.6%) and 25/26 (96.2%) on intention-to-treat and per-protocol basis, respectively. Conclusion: Eight-week course of daclatasvir and half-dose sofosbuvir is effective for acute hepatitis C in patients with eGFR <30 mL/min and could be a useful alternative to costly, kidney-safe anti-HCV oral drugs in resource-constrained settings. Graphical Abstract: